Kinematics and dynamics of mechanical systems : implementation in MATLAB and Simscape Multibody /: implementation in MATLAB and Simscape Multibody. (2022) - (Mechanical engineer), Russell, Kevin; (Mechanical engineer), Shen, Qiong; Sodhi, R. S (Raj S.)
No abstract available